Valori etici ed Europa nella crisi della globalizzazione - Vedovato, Giuseppe (Rivista di studi politici internazionali, 2010)
The substance of this article was delivered as a lectio magistralis by Giuseppe Vedovato when he received the Europa-Alcide De Gasperi prize for 2009 in recognition of his work promoting human rights and fundamental freedoms in Europe, together with his long standing battle on the subject of values. In his lectio he examines this dominant theme in relation to globalization and its new frontiers, from bioethics to the ethics of the environment and of communication, the ethics of the business world and those of agro-eco systems and he underscores the negative effect that the crisis of moral beliefs held in common is having. Within this overall picture the ethical principles of the Catholic Church are confirmed by experience and can be summed up in the principle of the common good, inspired by a respect for and the promotion of the individual and his/her fundamental rights. While financial globalization has taken over, inequality has increased and the young are losing their sense of values. The prime cause of this is, above all, the loss of a sense of collective belonging, replaced by rampant individualism, and a loss of respect for politics. The present model of development has deepened the gulf between a society of consumers that is overwhelmed by material goods and the rest who lack the bare minimum, while we seem unable to transform the idea of solidarity into social ethics. Globalization has advanced too fast for the development of the necessary regulations and the birth of a code of ethics that is valid the world over. It is up to Europe to assert the individual and universal values of human dignity, freedom, equality and solidarity, as well as the intangible dignity of the human being; but this too is full of contradictions which must be overcome. Europe should make use of the principle of subsidiarity and gain strength from the role played by Christianity in the unification of Europe. What we need is ideas not ideologies, because Europe will have to face tremendous challenges both within its frontiers and in the world outside. These challenges should be faced respecting certain priorities: the battle against unemployment and the preservation of social cohesion; a healthy and unified policy of immigration and asylum; the full application of the rules of competition in industry and a careful evaluation of the inefficient sectors of the market; an effective regulation regarding renewable energy that is compatible with the environment. Europe should also adopt a more stable stance on the international scene, and work for the definitive stability and association of the Western Balkans, while encouraging dialogue and cooperation with other countries of the world. It must invest in energy, research and technological development, in agriculture and European citizenship. The present crisis in globalization should be a stimulus for its mission in the world and endow the European Union with a well defined personality. These were the suggestions, based on the experience of the long-standing work of the Florentine-European who received the prize. RÉSUMÉ - L’article reproduit la lectio magistralis que Giuseppe Vedovato a donna quand le prix Europa-Alcide De Gasperi 2009 lui fut remis en reconnaissance de son engagement pour la défense des droits de l’homme et des libertés fondamentales en Europe et de son long combat sur le thème majeur des valeurs. La lectio analyse le thème des valeurs par rapport à la mondialisation, en mettant en évidence les nouvelles frontières de la bioéthique, de la morale environnementale, de l’éthique de la communication, de celle des affaires et de celle ayant un lien avec les écosystèmes tout en soulignant la crise des croyances morales communes. Dans ce contexte, les principes éthiques de l’Église catholique se trouvent confirmés par l’expérience et peuvent être synthétisés par le principe du bien commun qui s’inspire au respect de la personne et à la promotion de ses droits fondamentaux. La mondialisation financière fait rage, les inégalités augmentent et les jeunes générations sont en proie à une perte des valeurs. La perte du sens collectif au profit de l’individualisme, la désaffection à l’égard de la politique en sont les causes. Le modèle de développement a creusé un fossé profond entre la société de consommation, qui déborde de biens matériels, et celle privée du minimum nécessaire, pour laquelle la notion de solidarité peine à se définir comme éthique sociale. La mondialisation s’est développée sans qu’il n’y ait auparavant ni règlementations ni code éthique au niveau mondial. Il appartient à l’Europe de réaffirmer les valeurs individuelles et universelles de la dignité de l’homme, de la liberté, de l’égalité et de la solidarité. L’impalpable dignité de l’homme n’est pas, elle aussi, exempte de contradictions et elle doit apprendre à les dépasser. Pour ce faire, elle doit servir de levier au principe de subsidiarité et trouver de la force dans le rôle exercé par le christianisme dans le processus d’unification européenne. Il faut des idées et non des idéologies, parce que de grands défis attendent l’Europe à l’intérieur et à l’extérieur de ses frontières. Elle doit les affronter avec en priorité la lutte contre le chômage et la sauvegarde de la cohésion sociale, une saine et cohérente politique de l’immigration et de l’asile, l’application rigoureuse des règles de concurrence dans les entreprises de communication, l’évaluation attentive des secteurs inefficaces du marché financier, une normative efficace à l’égard des énergies renouvelables et compatibles avec l’environnement. L’Europe doit également avoir une position ferme sur la scène internationale, oeuvrer pour une stabilité définitive dans les Balkans, oeuvrer aussi pour le dialogue mondial et la coopération avec les pays tiers. Elle doit investir dans l’énergie, dans la recherche et le développement technologique, dans l’agriculture et dans la citoyenneté européenne. La crise actuelle de la mondialisation peut être l’occasion de poursuivre cette mission et en même temps donner à l’Europe un statut défini. Suggestions, tirées de l’expérience et du travail de longue haleine du Florentin-Européen à qui a été décerné ce prix.